MIP status of P. xylostella (L.) (Lepidoptera: Plutellidae) in Argentina. (FAVE Sección Ciencias Agrarias, 2019)
Diamond back moth (Plutella xylostella) is a cosmopolitan pest that causes intense damage to Brassicaceae crops, round the world. Features such as the short cycle, many generations per year, high fertility rate, helped that it has acquired resistance to many chemical insecticides, pure and in mixtures, including a biological like Bacillus thuringiensis. Despite its importance and being very studied abroad, in Argentina few studies have been carried out. The article analyzes the progress of the studies of this pest in Argentina, and gives guidelines that help its management.
Keywords: diamondback moth; management